Introduction Media and Information Literacy as a Public Good. - Jaakkola, Maarit; Durán-Becerra, Tomás (Corporación Universitaria Minuto de Dios - UNIMINUTO, 2023)
The theme of the 2021 edition of the Global Media and Information Literacy Week was “media and information literacy for the public good” (UNESCO, 2021b). The Republic of South Africa hosted the theme week to uphold the vision of information as a public good in the context of a new post-COVID normality (UNESCO, 2021a). In times of multiple crises, such as the COVID-19 pandemic, disinformation and information warfare, and in an era where the free flow of information is increasingly controlled and constrained, it is essential to discuss how good efforts of the humankind, such as democracy, freedom of speech, and MIL, can be saved as a public good, for the common good. The concern about MIL as a public good is dependent on appropriate structures for viable media that can sustain quality content, as well as accountability and public trust, and on citizens who can assess, nurture, and appreciate these (UNESCO, 2022). The Windhoek 30+ Declaration on Information as a Public Good (UNESCO, 2021d), which was announced at the World Press Freedom Day 2021 conference in Namibia, identified several factors as prerequisites for guaranteeing information as a public good that would “serve as a shared resource for the whole of humanity” (ibid., 4), including press freedom, media independence, plurality and viability, transparency of digital platforms, and citizens empowered by media and information literacy (MIL).
Capítulo completo en acceso abierto que hace parte de la obra Media and information literacy for the public good: UNESCO MILID Yearbook 2023.
Keywords: Bien público; Medios e información; Alfabetización; 374.0124; Literacy (Education) — Case Studies; Primary Education; Education and Development; Vocational Training; Media Literacy; Adult Literacy — Research